Antimicrobial Activity of Lipopeptide Biosurfactants Against Foodborne Pathogen and Food Spoilage Microorganisms and Their Cytotoxicity - Kourmentza, Konstantina; Gromada, Xavier; Michael, Nicholas; Degraeve, Charlotte; Vanier, Gaetan; Ravallec, Rozenn; Coutte, Francois; Karatzas, Kimon Andreas; Jauregi, Paula (Frontiers in Microbiology, 2021)
Lipopeptide biosurfactants produced by Bacillus sp. were assessed regarding their antimicrobial activity against foodborne pathogenic and food spoilage microorganisms. Both Gram-positive and Gram-negative bacteria were found not to be susceptible to these lipopeptides. However, mycosubtilin and mycosubtilin/surfactin mixtures were very active against the filamentous fungi Paecilomyces variotti and Byssochlamys fulva, with minimum inhibitory concentrations (MICs) of 1-16 mg/L. They were also active against Candida krusei, MIC= 16-64 mg/L. Moreover it was found that the antifungal activity of these lipopeptides was not affected by differences in isoform composition and/or purity. Furthermore their cytotoxicity tested on two different cell lines mimicking ingestion and detoxification was comparable to those of approved food preservatives such as nisin. Overall, for the first time here mycosubtilin and mycosubtilin/surfactin mixtures were found to have high antifungal activity against food relevant fungi at concentrations lower than their toxicity level hence, suggesting their application for extending the shelf-life of products susceptible to these moulds. In addition combining nisin with mycosubtilin or mycosubtiliin/surfactin mixtures proved to be an effective approach to produce antimicrobials with broader spectrum of action.